A numerical approach for assessing effects of shear on equivalent permeability and nonlinear flow characteristics of 2-D fracture networks. (January 2018) - Liu, Richeng; Li, Bo; Jiang, Yujing; Yu, Liyuan
Highlights: A numerical approach was developed to assess the effects of shear on hydraulic properties of 2D DFNs. A shear process significantly changes the permeability of DFNs in both linear and nonlinear regimes. Fracture surface roughness and variation of aperture in space can enhance inertial effects of flow. Shear-induced dislocation of flow paths changes the flow patterns in and around sheared intersections. Abstract: Hydro-mechanical properties of rock fractures are core issues for many geoscience and geo-engineering practices. Previous experimental and numerical studies have revealed that shear processes could greatly enhance the permeability of single rock fractures, yet the shear effects on hydraulic properties of fractured rock masses have received little attention. In most previous fracture network models, single fractures are typically presumed to be formed by parallel plates and flow is presumed to obey the cubic law. However, related studies have suggested that the parallel plate model cannot realistically represent the surface characters of natural rock fractures, and the relationship between flow rate and pressure drop will no longer be linear at sufficiently large Reynolds numbers. In the present study, a numerical approach was established to assess the effects of shear on the hydraulic properties of 2-D discrete fracture networks (DFNs) in both linear and nonlinear regimes. DFNs considering fracture surface roughness and variation of aperture in space were generated using an originally developed code DFNGEN. Numerical simulations by solving Navier–Stokes equations were performed to simulate the fluid flow through these DFNs. A fracture that cuts through each model was sheared and by varying the shear and normal displacements, effects of shear on equivalent permeability and nonlinear flow characteristics of DFNs were estimated. The results show that the critical condition of quantifying the transition from a linear flow regime to a nonlinear flow regime is: 10 −4 〈 J  < 10 −3, where J is the hydraulic gradient. When the fluid flow is in a linear regime (i.e., J  < 10 −4 ), the relative deviation of equivalent permeability induced by shear, δ 2, is linearly correlated with J with small variations, while for fluid flow in the nonlinear regime ( J 〉 10 −3 ), δ 2 is nonlinearly correlated with J . A shear process would reduce the equivalent permeability significantly in the orientation perpendicular to the sheared fracture as much as 53.86% when J  = 1, shear displacement D s  = 7 mm, and normal displacement D n  = 1 mm. By fitting the calculated results, the mathematical expression for δ 2 is established to help choose proper governing equations when solving fluid flow problems in fracture networks.